2014
DOI: 10.1186/1471-2334-14-277
|View full text |Cite
|
Sign up to set email alerts
|

The second generation of HIV-1 vertically exposed infants: a case series from the Italian Register for paediatric HIV infection

Abstract: BackgroundIn the Highly Active Antiretroviral Therapy (HAART) era, the prognosis of children perinatally infected with HIV-1 has significantly improved, so the number of perinatally-infected females entering child-bearing age and experiencing motherhood is increasing.MethodsA description of the medical history and pregnancy outcomes of women with perinatal acquired HIV-1 infection enrolled in the Italian Register for HIV infection in Children.ResultsTwenty-three women had 29 pregnancies. They had started an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
(26 reference statements)
3
6
0
2
Order By: Relevance
“…The median age of pregnant PHIV+ was similar to what was recently observed in the United States and Italy [ 11 , 14 ]. The median age of 8.3 years at HIV diagnosis was very close to 7.7 years reported for Italian pregnant PHIV+ [ 12 ], but slightly younger than age 10 years which we had observed in 2010 [ 4 ], pointing to a longer exposure time of ART use in the present population.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The median age of pregnant PHIV+ was similar to what was recently observed in the United States and Italy [ 11 , 14 ]. The median age of 8.3 years at HIV diagnosis was very close to 7.7 years reported for Italian pregnant PHIV+ [ 12 ], but slightly younger than age 10 years which we had observed in 2010 [ 4 ], pointing to a longer exposure time of ART use in the present population.…”
Section: Discussionsupporting
confidence: 84%
“…At enrollment, only 5/22 (23%) of PHIV+ had a VL below 50 copies/mL, but close to delivery this percentage increased to 41%. Our results are comparable to those from a US cohort that found 60% of pregnant PHIV+ with a VL below 400 copies/mL [ 11 ] and worse than a cohort from the United Kingdom where only 33% of PHIV+ pregnant had a viral load above 50 copies/mL near delivery [ 14 ].…”
Section: Discussionsupporting
confidence: 75%
“…Studies on pregnancy showed that its progression and outcomes are similar among PHIV women and women with sexually transmitted HIV, except for the proportion of women with undetectable viral load close to labor and delivery, which is lower among PHIV women [50][51][52] . The difficulty of attaining viral suppression in that population of pregnant women is probably due to their long previous exposure to various ART regimens, with the consequent emergence of resistance-related mutations in HIV; that fact also accounts for the high rate of cesarean deliveries in that group.…”
Section: Reproductive Healthmentioning
confidence: 99%
“…Creare una comunicazione tra diversi centri specifici produrrebbe un vantaggio per quei bambini che non sono più monitorati direttamente dal Registro in follow-up, in quando non infetti. Uno studio basato su dati del Registro di Calitri et al (8) ha documentato l'esito di gravidanze in donne con infezione perinatale già inserite nel Registro, che hanno successivamente partorito neonati non infetti, definendo un quadro di seconda generazione di esposti all'infezione all'HIV. Un altro obiettivo futuro che il Registro si pone è quello della possibilità di proseguire studi di farmacovigilanza in collaborazione con altri registri europei e di valutare la sorveglianza post-marketing dei farmaci antiretrovirali in pediatria.…”
Section: Il Futurounclassified